Bipolar Disorder With Psychotic Features and Ocular Toxoplasmosis: A Possible Pathogenetic Role of the Parasite? - Del Grande, Claudia; Contini, Carlo; Schiavi, Elisa; Rutigliano, Grazia; Maritati, Martina; Seraceni, Silva; Pinto, Barbara; Dell'Osso, Liliana; Bruschi, Fabrizio (J Nerv Ment Dis, 2017)
Recent evidence suggests the involvement of Toxoplasma gondii infection in the emergence of psychotic and affective disorders. In this report, we describe the case of a young Brazilian woman affected by recurrent ocular toxoplasmosis and presenting with a manic episode with psychotic features in the context of a diagnosis of Bipolar Disorder (BD), type I. We observed a relationship between ocular manifestations and the clinical course of bipolar illness, confirmed by molecular analyses (nested-PCR), as well as by the high level of T. gondii specific IgG. This case report is the first showing the presence of circulating parasite DNA at the time of occurrence of psychiatric symptoms, thus providing further support for a possible role of the parasite in the pathogenesis of some cases of BD.
Keywords: Adult; Bipolar Disorder; Brazil; Female; Humans; Toxoplasmosis, Ocular; Young Adult

Influence of vaginal lactoferrin administration on amniotic fluid cytokines and its role against inflammatory complications of pregnancy. - Maritati, Martina; Comar, Manola; Zanotta, Nunzia; Seraceni, Silva; Trentini, Alessandro; Corazza, Fabrizio; Vesce, Fortunato; Contini, Carlo (J Inflamm (Lond), 2017)
BACKGROUND: An altered amniotic cytokine profile has been reported in inflammatory pregnancy complications with a leading role for IL-6, a marker of the foetal systemic inflammatory response. Up to this date there is no exhaustive information neither on the foetal cytokine balance nor on the best method for its modulation. We aimed to evaluate the influence of vaginal lactoferrin administration on amniotic fluid concentration of 47 cytokines, chemokines and growth factors. METHODS: Sixty women undergoing genetic amniocentesis were enrolled in an open-label clinical trial. 300 mg of vaginal lactoferrin (Florence, Italy) were randomly administered to obtain 3 groups: A, 20 untreated patients; B and C (20 patients in each) respectively treated 4 and 12 h before amniocentesis. Cytokines, chemokines and growth factors concentrations were quantified by a magnetic bead Luminex multiplex immunoassays panel technology. Data analysis was performed with the software Stata (v. 13.1) and GraphPad Prism (v. 5). Group comparisons were performed using Kruskal-Wallis followed by Mann-Whitney U tests, with Bonferroni correction for multiple comparisons. A  < 0.05 was considered significant. RESULTS: Among the 47 tested mediators, 24 (51.06%) were influenced by lactoferrin. 11 (23.4%), showed a highly significant difference (p <0.001); among these IL-9, IL-15, IFN-γ, IP-10, TNF-α, IL-1α and MCP-3 underwent a down-regulation, while IL-17 and FGF-basic, G-CSF, GM-CSF an up-regulation. Difference between group C and both B and A was small for IL-15, IP-10, IL-1α, MCP-3, while it was negligible for IL-9, IFN-γ and TNF-α. IL-17 and the 3 growth factors were strongly enhanced in B and C groups. IL-17, FGF-basic and GM-CSF showed increasing concentrations in both B and C groups, while G-CSF resulted up-regulated only in group C. Significance was intermediate ( < 0.01) for the down regulated IL-2RA, IL-12p40 and IFNα2 (6.38%) while it was small for 10 mediators (21.27%) 7 of which (IL-2, IL-4, eotaxin, PDGF-BB, RANTES, IL-18 and MIF) down-regulated and 3 (MCP-1, IL-3, and SDF-1α) up-regulated. CONCLUSION: Lactoferrin down-regulates 17 pro-inflammatory amniotic mediators while up-regulating 7 anti-inflammatory amniotic mediators, 5 of which definitively belonging to an anti-inflammatory profile. These findings open to clinical investigation on its use against inflammatory complications of pregnancy.

Anti-ApoA-1 IgG serum levels predict worse poststroke outcomes. - Carbone, Federico; Satta, Nathalie; Montecucco, Fabrizio; Virzi, Julien; Burger, Fabienne; Roth, Aline; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; et al. (Eur J Clin Invest, 2016)
BACKGROUND: Autoantibodies to apolipoprotein A-1 (anti-ApoA-1 IgG) were shown to predict major adverse cardiovascular events and promote atherogenesis. However, their potential relationship with clinical disability and ischaemic lesion volume after acute ischaemic stroke (AIS) remains unexplored. MATERIALS AND METHODS: We included n = 76 patients admitted for AIS and we investigated whether baseline serum anti-ApoA-1 IgG levels could predict (i) AIS-induced clinical disability [assessed by the modified Rankin Scale (mRS)], and (ii) AIS-related ischaemic lesion volume [assessed by Computed Tomography (CT)]. We also evaluated the possible pro-apoptotic and pro-necrotic effects of anti-ApoA-1 IgG on human astrocytoma cell line (U251) using flow cytometry. RESULTS: High levels of anti-ApoA-1 IgG were retrieved in 15·8% (12/76) of patients. Increased baseline levels of anti-ApoA-1 IgG were independently correlated with worse mRS [β = 0·364; P = 0·002; adjusted odds ratio (OR): 1·05 (95% CI 1·01-1·09); P = 0·017] and CT-assessed ischaemic lesion volume [β = 0·333; P < 0·001; adjusted OR: 1·06 (95% CI 1·01-1·12); P = 0·048] at 3 months. No difference in baseline clinical, biochemical and radiological characteristics was observed between patients with high vs. low levels of anti-ApoA-1 IgG. Incubating human astrocytoma cells with anti-ApoA-1 IgG dose dependently induced necrosis and apoptosis of U251 cells in vitro. CONCLUSION: Anti-ApoA-1 IgG serum levels at AIS onset are associated with poorer clinical recovery and worse brain lesion volume 3 months after AIS. These observations could be partly explained by the deleterious effect of anti-ApoA-1 IgG on human brain cell survival in vitro and may have clinical implication in the prediction of poor outcome in AIS.

HPV genotypes distribution in Chlamydia trachomatis co-infection in a large cohort of women from north-east Italy. - Seraceni, Silva; Campisciano, Giuseppina; Contini, Carlo; Comar, Manola (J Med Microbiol, 2016)
Human papillomavirus (HPV) and Chlamydia trachomatis are pathogens with oncogenic potential associated with persistent infections. Epidemiological data on C. trachomatis infection status, C. trachomatis/HPV co-infection and the relationship between HPV genotypes in Italian women are only preliminary. The aim of the present study was to characterize the relationship between HPV genotypes and C. trachomatis in an extending cohort of asymptomatic immunocompetent women from an area of north-east Italy. A retrospective study was conducted using Luminex technology on cervical swabs from asymptomatic immunocompetent women, comprising 921 attending the prevention centre for the Cervical Cancer Program and 6214 who had been referred to the Sexually Transmitted Infections Center, with clinical indications of HPV and C. trachomatis infections. A quantitative real-time PCR was performed to assess chronic C. trachomatis infection by heat-shock protein 60 (Hsp60) gene expression. The overall prevalence of the investigated pathogens was 39 % (359/921) for HPV and 4 % (251/6214) for C. trachomatis. The Hsp60 gene was detected in 57 % of the women infected with C. trachomatis. HPV co-infection was present in 58 % of C. trachomatis-infected women. A high prevalence of co-infection was found in women with chronic C. trachomatis infection (68 %, P = 0.0002), especially in women ≤ 25 years (72 %) where HPV multiple infections were found in 78 % (P = 0.022). HPV genotype distribution showed that uncommon low-risk genotypes were associated with C. trachomatis. These results indicate a high frequency of co-detection of multiple HPV genotypes in chronically infected young women and suggest that the expression of the C. trachomatis Hsp60 gene may favour HPV infection.

Association Study between Cervical Lesions and Single or Multiple Vaccine-Target and Non-Vaccine Target Human Papillomavirus (HPV) Types in Women from Northeastern Brazil. - Chagas, Bárbara Simas; Comar, Manola; Gurgel, Ana Pavla Almeida Diniz; Paiva, Sérgio; Seraceni, Silva; de Freitas, Antonio Carlos; Crovella, Sergio (PLoS One, 2015)
We performed an association between high-grade squamous intraepithelial lesions (HSIL), low-grade squamous intraepithelial lesions (LSIL) and single or multiple vaccine-target as well as non-vaccine target Human papillomavirus (HPV) types. Using bead-based HPV genotyping, 594 gynecological samples were genotyped. An association between squamous intraepithelial lesion (SIL) and presence of HPV16, 18, 31, 58 and 56 types were calculated. The risk was estimated by using odds ratio (OR) and 95% of confidence intervals (CI). A total of 370 (62.3%) women were HPV positive. Among these, 157 (42.7%) presented a single HPV infection, and 212 (57.3%) were infected by more than one HPV type. HPV31 was the most prevalent genotype, regardless single and multiple HPV infections. Single infection with HPV31 was associated with LSIL (OR=2.32; 95%CI: 1.01 to 5.32; p=0.04); HPV31 was also associated with LSIL (OR=3.28; 95%CI: 1.74 to 6.19; p= 0.0002) and HSIL (OR=3.82; 95%CI: 2.10 to 6.97; p<0.001) in multiple HPV infections. Risk to harbor cervical lesions was observed in multiple HPV infections with regard to the HPV56 (OR=5.39; 95%CI: 2.44 to 11.90; p<0.001for LSIL; OR=5.37; 95%CI: 2.71 to 10.69; p<0.001) and HPV58 (OR=3.29; 95%CI: 1.34 to 8.09; p=0.0091 for LSIL; OR=3.55; 95%CI: 1.56 to 8.11; p=0.0026) genotypes. In addition, women coinfected with HPV16/31/56 types had 6 and 5-fold increased risk of HSIL (OR=6.46; 95%CI: 1.89 to 22.09; p=0.002) and LSIL (OR=5.22; 95%CI: 1.10 to 24.70; p=0.03), respectively. Multiple HPV infections without HPV16/18 has 2-fold increased risk of HSIL (OR=2.57; 95%CI: 1.41 to 4.70; p=0.002) and LSIL OR=2.03; 95%CI: 1.08 to 3.79; p=0.02). The results of this study suggest that single and multiple vaccine target as well as non-vaccine target HPV types are associated with LSIL and HSIL. These finding should be taken into consideration in the design of HPV vaccination strategies.

Leptin/adiponectin ratio predicts poststroke neurological outcome. - Carbone, Federico; Burger, Fabienne; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; Bertolotto, Maria; Dallegri, Franco; Mach, François; Fainardi, Enrico; et al. (Eur J Clin Invest, 2015)
BACKGROUND AND AIMS: Different adipokines have been associated with atherosclerotic plaque rupture and cardiovascular events, such as acute ischaemic stroke (AIS). However, the potential role of these molecules in postischaemic brain injury remains largely unknown. METHODS AND METHODS: We performed a substudy analysis on nonobese patients with first atherothrombotic stroke (n = 35) from a recently published prospective cohort. Primary endpoint was to investigate the predictive value of serum leptin/adiponectin ratio on neurological recovery at 90 days after AIS. The secondary endpoint was the predictive value of serum adipokine levels of clinical and radiological outcomes at a shorter follow-up (at days 1 and 7 after AIS). The radiological evaluation included ischaemic lesion volume and haemorrhagic transformation (HT). The clinical examination was based on National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS). RESULTS: At day 1 after AIS, serum leptin and leptin/adiponectin ratio were increased and inversely correlated with both radiological and clinical parameters at all follow-up time points. Once identified the best cut-off points by receiver operating characteristic (ROC) analysis, risk analysis showed that higher circulating leptin improved neurological recovery at day 90. In addition, leptin/adiponectin ratio maintained statistical significance after adjustment for age, gender and thrombolysis, also predicting the occurrence of HT in the first 7 days after AIS (adjusted OR 0·15 [95% CI 0·03-0·83); P = 0·030]). CONCLUSIONS: Higher leptin/adiponectin ratio at day 1 predicted better neurological outcomes in patients with atherothrombotic AIS and might be potentially useful as a prognostic biomarker of the disease.

HPV and Chlamydia trachomatis co-detection in young asymptomatic women from high incidence area for cervical cancer. - Bellaminutti, Serena; Seraceni, Silva; De Seta, Francesco; Gheit, Tarik; Tommasino, Massimo; Comar, Manola (J Med Virol, 2014)
Chlamydia trachomatis causing chronic inflammatory diseases has investigated as possible human papillomavirus (HPV) cofactor in cervical cancer. The aim of this study is to evaluate the prevalence of Chlamydia trachomatis and HPV co-infection in different cohorts of asymptomatic women from a Northern Italy area at high incidence for cervical cancer. Cervical samples from 441 females were collected from Cervical Cancer Screening Program, Sexually Transmitted Infectious and Assisted Reproductive Technology centres. HPV and Chlamydia trachomatis were detected simultaneously and genotyped using a highly sensitive bead based assay. The overall prevalence of Chlamydia trachomatis was estimated 9.7%, in contrast with the reported national data of 2.3%, and co-infection with HPV was diagnosed in the 17% of the samples. In females ≤ 25 years of age, the infection reached a peak of 22% and co-infection with HPV of 45.8% (P < 0.001). Of note, in young females diagnosed with low grade cervical lesions, no significant difference between Chlamydia trachomatis and HPV distribution was observed, while differently, HPV co-infection was found significantly associated to the presence of intraepithelial lesions when compared to older females (20% vs. 1%; P < 0.001). In this study, the use of a high sensitive molecular technique exhibited higher analytical sensitivity than the referred assays for the diagnosis of Chlamydia trachomatis and HPV co-infection in asymptomatic females, leading to reduction of the potential to identify incorrectly the infection status. An active screening for timely treatment of Chlamydia trachomatis infection is suggested in young females to evaluate a possible decrease in incidence of pre-cancer intraepithelial lesions.
Keywords: Adolescent; Adult; Age Factors; Cervix Uteri; Chlamydia Infections; Chlamydia trachomatis; Coinfection; Female; Genotype; Humans; Incidence; Italy; Middle Aged; Papillomaviridae; Papillomavirus Infections; Prevalence; Young Adult